Mencegah Radikalisme Perspektif Pendidikan Islam - Rizqi Al-Ali, Muhammad; Larasati, Ayu; Ardino, Zidane; Zahroh, Nabilla (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2025)
The phenomenon of radicalism that has infiltrated the world of education is a serious problem because it can disrupt the process of character formation of students and threaten national values. This study aims to explore how the pedagogical approach in Islamic Religious Education can protect students from radicalism through instilling moderate, tolerant, and contextual Islamic values. This study uses a qualitative method with a library research approach enriched with field data from observations, interviews, and documentation at SMP NEGERI 28 MEDAN. Descriptive-analytical analysis to interpret key concepts and their implementation in the school environment. The research findings indicate that efforts to prevent radicalism through Islamic education can be carried out effectively through various strategies, such as strengthening a moderation-based curriculum, empowering teachers as facilitators of religious dialogue, and implementing participatory and reflective learning methods. The values of tasamuh (tolerance), i'tidal (justice), and rahmah (compassion) are the main foundations in building students' critical awareness. In addition, the use of digital media in an educational manner has been proven to help students sort out extreme religious information.